Agency and Communion as Fundamental Dimensions of Social Judgment - and Bogdan Wojciszke's Brilliant Idea on Perspective - Abele, Andrea E. (Social Psychological Bulletin, 2022)
The fundamental dimensions of social judgment and social evaluation, called agency and communion, are overarching constructs in many fields of psychology. Agency is related to goal-striving and "getting ahead", communion is related to forming bonds and "getting along". These dimensions are used both to interpret behaviors, and to evaluate targets. Bogdan Wojciszke was the first to relate these dimensions to perspective, and to show that the perspective of an actor is more closely related to agency, whereas the perspective of an observer is more closely related to communion. The "Dual Perspective Model" combines the fundamental dimensions of social judgment and evaluation with perspective and leads to a number of far-reaching hypotheses on social interactions. The model has inspired research in diverse areas of psychology, such as evaluation of brands, stereotypes of groups, evaluation of political leaders, gender research, social desirability research, self-evaluation, bodily posture in social interaction, to name just a few. It has been further developed to a broad-ranging theory applicable to many phenomena in (social) psychology. Bogdan Wojciszke lives his ideals and it is a pleasure and an honor to cooperate with him.
CRIS-Team Scopus Importer:2022-12-02
Keywords: actor versus observer perspective; agency and communion; application and extension of the model; dual perspective model; fundamental dimensions of social judgment